Hungarian Monitoring, 11 March 1989 . [Magyar rádiófigyelő], 1989. március 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Dick Cheney the new candidate for American defense minister - Wages strike in Poland - Pakistani foreign minister travels to Tehran - USSR before the elections - Tensions between the two German states - Ota Sik and his "third way" ideas Domestic Affairs: - Károly Grósz party general secretary calls again for joint March 15 celebrations - Hungarian Democratic Front forms committee to prepare for organizing as a party - Interview with Rezső Nyers on, among other things, who wants to leave Hungarian Socialist Workers' Party (MSZMP) and why - Where and how does the Party's reform wing wish to concentrate its forces? minister of state Imre Pozsgay - István Sarlós distances himself from Ferenc Münnich Society and states that he believes in the multi-party system - Hungarian Democratic Forum (MDF) congress report - Transylvanian refugees hold meeting in Veszprém Economy: - How does American guest professor at the managerial training school see the state of and chances for the Hungarian economy? Külpolitika: - D. Cheney az új jelölt az amerikai honvédelmi miniszterségre - Bérsztrájk Lengyelországban - A pakisztáni külügyminiszter teheráni útja - A szovjet választások elé - Feszültségek a két német állam kapcsolatában - Ota Sik és az általa elképzelt "harmadik út" Belpolitika: - Grósz Károly pártfőtitkár ismét március 15-e közös megünneplésére szólított fel - A MDF bizottságot hozott létre a párt szerveződés előkészítésére - Interjú Nyers Rezsővel, aki többek között elmondja, kik és miért akarnak kilépni az MSZMP-ből - A párt reformszárnya hol és milyen módon kívánja gyülekeztetni erőit? - Nyilatkozik Pozsgay Imre államminiszter - Sarlós István elhatárolja magát a Münnich Ferenc Társaságtól, és kijelenti, hogy a többpártrendszer híve - Az MDF-kongresszus beszámolója - Erdélyi menekültek tartottak találkozót Veszprémben Gazdaság: - Hogyan látja a magyar gazdaság helyzetét, lehetőségeit egy amerikai vendégprofesszor a menedzserképző iskolán?